2020
DOI: 10.1177/0896860820927534
|View full text |Cite
|
Sign up to set email alerts
|

Ten-year survival of patients treated with peritoneal dialysis: A prospective observational cohort study

Abstract: Background: Few studies evaluated over 5-year outcomes of dialysis patients. This study examined 10-year all-cause mortality and death-censored technique failure in a cohort of incident peritoneal dialysis (PD) individuals. Methods: Five hundred and thirty-three incident PD individuals from 2006 to 2008 were prospectively followed up for more than 10 years until 2018. Clinical characteristics at PD initiation were collected. The primary outcome was all-cause mortality, and the secondary outcome was death-censo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
2
7
0
Order By: Relevance
“…In this study, nephrologists perceived long-term PD as around 5 years, which is consistent with definitions used in the literature 22. However, participant responses may be influenced by their clinical observations and context rather than published evidence, given that 5-year technique survival rates vary globally, from 16% in Australia to 85% in China 13 23. Participants also highlighted the differences in knowledge of PD among nephrologists, and the impact this may have on the care of patients receiving PD.…”
Section: Discussionsupporting
confidence: 75%
“…In this study, nephrologists perceived long-term PD as around 5 years, which is consistent with definitions used in the literature 22. However, participant responses may be influenced by their clinical observations and context rather than published evidence, given that 5-year technique survival rates vary globally, from 16% in Australia to 85% in China 13 23. Participants also highlighted the differences in knowledge of PD among nephrologists, and the impact this may have on the care of patients receiving PD.…”
Section: Discussionsupporting
confidence: 75%
“…Adragao score measures VC and therefore may estimate CVD risk in CKD patients through hands and pelvic radiographies. Charlson Comorbidity Index predicts 10-year survival in patients with multiple comorbidities and has been useful in the prediction of mortality risk in CKD patients [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Xia et al. 15 found that diabetic nephropathy was an independent risk factor for technical failure of catheterization. Many studies have also shown that diabetes mellitus is a risk factor for peritonitis after catheterization.…”
Section: Discussionmentioning
confidence: 99%
“…We found that systolic blood pressure and the rate of diabetes mellitus were significantly higher in patients with early complications than in those without early complications. Xia et al 15 found that diabetic nephropathy was an independent risk factor for technical failure of catheterization. Many studies have also shown that diabetes mellitus is a risk factor for peritonitis after catheterization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation